Increased Prevalence of Inflammatory Bowel Disease in Patients with Mutations in Genes Encoding the Receptor Subunits for TGFβ. Issue 9 (September 2016) - Guerrerio, Anthony L.; Frischmeyer-Guerrerio, Pamela A.; Huang, Chengrui; Wu, Yuqiong; Haritunians, Talin; McGovern, Dermot P. B.; MacCarrick, Gretchen L.; Brant, Steven R.; Dietz, Harry C.
Abstract : Background: TGFβ is a multifunctional cytokine that is critical in regulating mucosal immunity. Murine studies have revealed that disruption of canonical TGFβ signaling leads to systemic inflammation including colitis. Loeys–Dietz syndrome (LDS) results from heterozygous mutations in the genes encoding the subunits of the TGFβ receptor. Methods: All patients with confirmed mutations in TGFBR1 or TGFBR2, seen in the Johns Hopkins Connective Tissue Disorders clinic, were asked to participate in the study. Ninety-three consecutive patients were enrolled, including 4 with inflammatory bowel disease (IBD). Using the Illumina Immunochip array, we undertook an exploratory analysis to evaluate the potential genetic risk factors that could predict which patients with LDS would develop IBD. Results: We report an increased prevalence of IBD in patients with LDS types I and II. We describe the course of several patients. In this small sample, the 3 whites with IBD had a genetic risk score in the top 6 highest scores of patients evaluated. Conclusion: We report a 10-fold increase in the prevalence of IBD in patients with LDS compared with the general population. Onset of disease in 3 of the 4 patients was at less than 18 years, and the clinical course in 2 of the 4 was severe with a poor response to traditional medications. Further evaluation of the genetic risk score is needed to determine whether it can predict which patients with LDS are most likely to develop IBD. This case series of patients with LDS with IBD suggests that defective TGFβ signaling may have an influence on IBD risk. Abstract : Article first published online 9 August 2016.